Association of Gray Matter Atrophy Patterns With Clinical Phenotype and Progression in Multiple Sclerosis. (16th March 2021) - Rocca, Maria A.; Valsasina, Paola; Meani, Alessandro; Gobbi, Claudio; Zecca, Chiara; Rovira, Alex; Sastre-Garriga, Jaume; Kearney, Hugh; Ciccarelli, Olga; Matthews, Lucy; Palace, Jacqueline; Gallo, Antonio; et al.
Abstract : Objectives: Gay matter (GM) involvement is clinically relevant in multiple sclerosis (MS). Using source-based morphometry (SBM), we characterized GM atrophy and its 1-year evolution across different MS phenotypes. Methods: Clinical and MRI data were obtained at 8 European sites from 170 healthy controls (HCs) and 398 patients with MS (34 with clinically isolated syndrome [CIS], 226 with relapsing-remitting MS [RRMS], 95 with secondary progressive MS [SPMS], and 43 with primary progressive MS [PPMS]). Fifty-seven HCs and 144 with MS underwent 1-year follow-up. Baseline GM loss, atrophy progression, and correlations with disability and 1-year clinical worsening were assessed. Results: SBM identified 26 cerebellar, subcortical, sensory, motor, and cognitive GM components. GM atrophy was found in patients with MS vs HCs in almost all components ( p range <0.001–0.04). Compared to HCs, patients with CIS showed circumscribed subcortical, cerebellar, temporal, and salience GM atrophy, while patients with RRMS exhibited widespread GM atrophy. Cerebellar, subcortical, sensorimotor, salience, and frontoparietal GM atrophy was found in patients with PPMS vs HCs and in patients with SPMS vs those with RRMS. At 1 year, 21 (15%) patients had clinically worsened. GM atrophy progressed in MS in subcortical, cerebellar, sensorimotor, and fronto-temporo-parietal components. Baseline higher disability was associated ( R 2 = 0.65) with baseline lower normalized brain volume (β = −0.13, p = 0.001), greater sensorimotor GM atrophy (β = −0.12, p = 0.002), and longer disease duration (β = 0.09, p = 0.04). Baseline normalized GM volume (odds ratio 0.98, p = 0.008) and cerebellar GM atrophy (odds ratio 0.40, p = 0.01) independently predicted clinical worsening (area under the curve 0.83). Conclusion: GM atrophy differed across disease phenotypes and progressed at 1 year in MS. In addition to global atrophy measures, sensorimotor and cerebellar GM atrophy explained baseline disability and clinical worsening.